From Embryo to Adult: piRNA-Mediated Silencing throughout Germline Development in Drosophila - Pauline P. Marie; Stéphane Ronsseray; Antoine Boivin (G3: Genes, Genomes, Genetics, 2017)
In metazoan germ cells, transposable element activity is repressed by small noncoding PIWI-associated RNAs (piRNAs). Numerous studies in Drosophila have elucidated the mechanism of this repression in the adult germline. However, when and how transposable element repression is established during germline development has not been addressed. Here, we show that homology-dependent trans silencing is active in female primordial germ cells from late embryogenesis through pupal stages, and that genes related to the adult piRNA pathway are required for silencing during development. In larval gonads, we detect rhino-dependent piRNAs indicating de novo biogenesis of functional piRNAs during development. Those piRNAs exhibit the molecular signature of the “ping-pong” amplification step. Moreover, we show that Heterochromatin Protein 1a is required for the production of piRNAs coming from telomeric transposable elements. Furthermore, as in adult ovaries, incomplete, bimodal, and stochastic repression resembling variegation can occur at all developmental stages. Clonal analysis indicates that the repression status established in embryonic germ cells is maintained until the adult stage, suggesting the implication of a cellular memory mechanism. Taken together, data presented here show that piRNAs and their associated proteins are epigenetic components of a continuous repression system throughout germ cell development.